1981
DOI: 10.1021/bi00526a020
|View full text |Cite
|
Sign up to set email alerts
|

Structure of chromatin at deoxyribonucleic acid replication forks: prenucleosomal deoxyribonucleic acid is rapidly excised from replicating simian virus 40 chromosomes by micrococcal nuclease

Abstract: Replicating simian virus 40 (SV40) chromosomes were found to be similar to other eukaryotic chromosomes in that the rate and extent of micrococcal nuclease (MNase) digestion were greater with replicating than with nonreplicating mature SV40 chromatin. MNase digestion of replicating SV40 chromosomes, pulse labeled in either intact cells or nuclear extracts, resulted in the rapid release of nascent DNA as essentially bare fragments of duplex DNA (3-7S) that had an average length of 120 base pairs and were degrad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
36
0

Year Published

1983
1983
2010
2010

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 57 publications
(106 reference statements)
4
36
0
Order By: Relevance
“…If HSF invades Nuc Ϫ2 and directly binds its target sequences, then its binding to nucleosomal DNA would be cell cycle independent. Alternatively, HSF might preempt the assembly of Nuc Ϫ2, either by binding DNA immediately following replication, when histone octamers are transiently displaced from the newly synthesized DNA (13,32,63; but see reference 8), or by binding to the nascent nucleosome shortly thereafter, aborting its maturation. Either way, such binding would be cell cycle dependent.…”
Section: Resultsmentioning
confidence: 99%
“…If HSF invades Nuc Ϫ2 and directly binds its target sequences, then its binding to nucleosomal DNA would be cell cycle independent. Alternatively, HSF might preempt the assembly of Nuc Ϫ2, either by binding DNA immediately following replication, when histone octamers are transiently displaced from the newly synthesized DNA (13,32,63; but see reference 8), or by binding to the nascent nucleosome shortly thereafter, aborting its maturation. Either way, such binding would be cell cycle dependent.…”
Section: Resultsmentioning
confidence: 99%
“…Experiments were performed in which the cells had been A~25 [3][4][5][6] after drug treatment for 60 min, as expected because there were fewer molecules to ligate at that time.…”
Section: Resultsmentioning
confidence: 99%
“…For example, the replication fork of simian virus 40 DNA has been analyzed by using several different nucleases. Recently it was shown that one can subdivide the simian virus 40 replication fork into a prenucleosomal DNA region and immature and mature chromatin (3), and the unique DNA sequences at the origin of DNA replication have been identified (4).…”
mentioning
confidence: 99%
“…One early model proposed that the old histones cover the leading strand of the replication fork while newly synthesized histones complex with the lagging strand (Seale, 1976;Riley and Weintraub, 1979;Seidman et al, 1979). However, after a period of debate, the field has finally reached to the conclusion (McKnight and Miller, 1977;Cusick et al, 1981Cusick et al, , 1984Fowler et al, 1982;Pospelov et al, 1982;Annunziato and Seale, 1984;Jackson and Chalkley, 1985) that parental histones are randomly distributed to both leading and lagging strands. Most of the early studies on parental histone segregation were carried out in cycling cells with the treatment of protein synthesis inhibitors, such as cycloheximide and puromycin.…”
Section: Early Investigations On Rc Nucleosome Assembly and Their Conmentioning
confidence: 99%